A Bibliometric and Visualized Analysis of Mobile Banking Research Using VOSviewer - Melly Susanti; Heru Kreshna Reza (PT FORMOSA CENDEKIA GLOBAL, 2022)
Mobile banking as an innovative delivery channel for financial services, especially in developing countries. Mobile banking is the latest technological innovation, to streamline bank operations. Biometrics is an emerging technology in the era of the internet and mobile communications. The purpose of this study was to determine the development of research related to mobile banking. Bibliometrics is effective in providing datasets that can be used to improve the quality of research. By using Bibliometrics and publication trends in the Scopus database, the data is processed using VOSViewer software to view network visualizations, density visualizations and overlay visualizations.